Evaluasi Servqual pada Petshop Indonesia menggunakan Metode IPA dan CSI - Widiyanti, Wiwik (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2022)
Pet Shop is very important existence for animal lovers because it provides all the needs of animals from food to pet health. Therefore, each petshop competes in competing to maintain it. This can be done by regularly competing with each other for the quality of service from the petshop. One that conducts periodic evaluations is Petshop Indonesia. This is deemed necessary because there are still complaints submitted to employees regarding Petshop Indonesia services. The purpose of this study is the attributes that must be improved and maintained and to find out how big the consumer satisfaction index is. While the research method used is quantitative research with the analytical methods used are Importance Performance Analysis (IPA) and Customer Satisfied Index (CSI). The research results obtained are that there are six attributes that need to be improved. The six attributes are the availability of boxes and criticisms, employee submissions, speed of responding to customers, confidentiality of customer data, paying attention to suggestions and criticisms, and services that do not differentiate status. The CSI obtained is included in the satisfaction criteria. The new thing in this research is that there is no servqual evaluation research in a petshop using the IPA and CSI methods.